2020
DOI: 10.1088/1748-9326/ab65cc
|View full text |Cite
|
Sign up to set email alerts
|

Radiance-based NIRv as a proxy for GPP of corn and soybean

Abstract: Substantial uncertainty exists in daily and sub-daily gross primary production (GPP) estimation, which dampens accurate monitoring of the global carbon cycle. Here we find that near-infrared radiance of vegetation (NIR v,Rad ), defined as the product of observed NIR radiance and normalized difference vegetation index, can accurately estimate corn and soybean GPP at daily and half-hourly time scales, benchmarked with multi-year tower-based GPP at three sites with different environmental and irrigation condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 62 publications
(24 reference statements)
5
52
0
Order By: Relevance
“…S8b) cannot be easily explained by invoking SIF retrieval noise and therefore other potential reasons for these differences should be investigated. Our results on the direct comparison of SIF and NIRVP for GPP estimation confirm and considerably extend previous findings from site-level studies 22,40,41 . Among other things, we confirmed that previous site-level results showing better GPP estimation performance of NIRVP compared to SIF in crops 22,40 also held in a Mediterranean grassland site which experiences drought (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…S8b) cannot be easily explained by invoking SIF retrieval noise and therefore other potential reasons for these differences should be investigated. Our results on the direct comparison of SIF and NIRVP for GPP estimation confirm and considerably extend previous findings from site-level studies 22,40,41 . Among other things, we confirmed that previous site-level results showing better GPP estimation performance of NIRVP compared to SIF in crops 22,40 also held in a Mediterranean grassland site which experiences drought (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…S1a). Regarding the correlations of SIF and NIRVP to GPP, two previous studies 22,40 already reported higher or similar correlation of NIRVP for the rice, wheat, soybean and the two corn datasets we used. In addition, we found that NIRVP outperformed SIF also for the grassland site (R 2 = 0.60 vs. 0.49 for half-hourly data; Fig.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations